Assessment of Perception of Sexually Transmitted Infections among Urban Women: A Cross-Sectional Study (Bangladesh Medical Journal, 2025)
Public health concerns about sexually transmitted infections (STIs) are becoming more widespread, particularly in developing countries with dense populations and high rates of population mobility. Their prevalence rises with widespread exposure to risk factors. Promoting knowledge and comprehension of STI prevention is essential to shielding women of reproductive age groups (15-45 years) from its harmful effects. This household-based cross-sectional study was directed to assess the level of perception of sexually transmitted infections among 273 purposively selected urban women residing in Moghbazar, Malibagh, and Shantibagh areas of Dhaka South City Corporation, Bangladesh. Data were collected using a pre-tested semi-structured questionnaire based on participants' convenience. The participants had a mean age of 32.8±4.2 years, ranging from 18 to 45 years, with the maximum (40.3%) of them were in age group 31-40 years. In terms of education, over half (54.6%) had completed secondary education, mostly similar to their partners (52.7%) and their average monthly household income was 18765.2±3262.8 BDT. The mean age at marriage was 19.8±2.1 years, with 10.3% marrying before 18. The average duration of marriage was 9.2±6.3 years. The most commonly used contraceptive methods were oral pills (60.4%) and condoms (41.0%). Majority of the women (51.3%) had a poor perception of STIs, while more than one-third (36.1%) had an average perception, and 12.6% had a good perception. The level of STIs perception among women was significantly associated with age, education, spouse's education, and marital duration (p